Influence of Ag alloying on the morphology, structure, mechanical properties, thermal stability and oxidation resistance of multilayered TiSiN/Ti(Ag)N films. (July 2020) - AL-Rjoub, A.; Cavaleiro, A.; Fernandes, F.
Abstract: Self-lubricant films combine the intrinsic properties of high oxidation resistance coatings with lubricious elements deposited as monolayer and/or multilayered configuration, offering an opportunity to design green coating materials. The present paper reports the influence of Ag additions (range 0–3.2 at.%), considered as low friction material, on the morphology, structure, mechanical properties, thermal stability and oxidation resistance of multilayered TiSiN/TiN(Ag) films deposited by sputtering. The surface morphology of the coatings progressively changed from a well-defined cauliflower structure to a tetrahedral and pyramid-like structure and the cross-section morphology became more compact with Ag incorporation. A decrease of coating's hardness and Young's modulus was observed with Ag additions, due to the incorporation of the soft silver on the structure. The coatings showed excellent thermal stability and revealed a good control to the Ag diffusion towards the surface in protective atmosphere. Ag additions did not affect the onset oxidation point of films. However, the oxidation resistance of the films was reduced with Ag inclusion, due to its additional transportation during the oxidation process, promoting additional paths for ions diffusion, giving rise to a less protective Ti-Si-O layer and contributing to the formation of big crystals of rutile on the top. Graphical abstract: Unlabelled Image Highlights: Mechanical properties of the TiSiN/Ti(Ag)N films are negatively affected by Ag incorporation A multilayered TiSiN/Ti(Ag)N design offers an effective barrier to Ag diffusion. Annealing treatment promotes an increase of films crystallinity and hardness. Ag incorporation does not affect the onset point of oxidation at high temperatures of the films. During oxidation, the presence of Ag in the TiSiN/Ti(Ag)N films gives rise to a less protective Ti-Si-O layer